2000
DOI: 10.1212/wnl.54.8.1616
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying fluctuation in dementia with Lewy bodies, Alzheimer’s disease, and vascular dementia

Abstract: Standardized assessment methods demonstrate that FC is significantly more common and severe in DLB than in other major dementias. The periodicity of FC is different in DLB and VaD cases, with important implications for the underlying causal mechanisms and for differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
177
3
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(191 citation statements)
references
References 36 publications
9
177
3
2
Order By: Relevance
“…The questionnaires are able to discriminate 85% of DLB patients, as confirmed by autopsy [7]. Cognitive fluctuations are considered a clinical feature typical of DLB, described in 70-80% of these patients, only in 14-20% of AD patients and in 15-30% of VaD subjects [8].…”
Section: Synucleinopathies: Dementia With Lewy Bodiesmentioning
confidence: 87%
See 1 more Smart Citation
“…The questionnaires are able to discriminate 85% of DLB patients, as confirmed by autopsy [7]. Cognitive fluctuations are considered a clinical feature typical of DLB, described in 70-80% of these patients, only in 14-20% of AD patients and in 15-30% of VaD subjects [8].…”
Section: Synucleinopathies: Dementia With Lewy Bodiesmentioning
confidence: 87%
“…Only in 3 of the DLB patients presenting with R2 delays, discrepant latencies on the two sides of stimulation were found [8], yet ipsilateral and contralateral responses were always overlapping, thus it is likely that the afferent pathway is prominently involved in DLB. In a successive study we tested the supposition that BR alterations present in DLB patients are sensitive to cholinergic modulation.…”
Section: Blink Reflex Abnormalitiesmentioning
confidence: 94%
“…The working group concluded that existing testing procedures (e.g., the Alzheimer's disease assessment scale) do not properly identify all cognitive deficits characterizing AD patients, in particular attention deficits, and has recommended that automated procedures be used alongside more traditional ones to ultimately determine whether they should supersede traditional methods [9]. The CDR system has shown sensitivity in identifying mild cognitive impairment [27,41] and is able to differentiate various types of dementia (AD, DLB, VD, Huntington's Chorea [25,[35][36][37][38]). The CDR system measures therapeutic response to a variety of medications in both AD [2,7,24,32,34] and DLB [22] and shows superior sensitivity in identifying AD and Huntington's disease as compared to all the most widely used non-automated procedures [25].…”
Section: The Cdr Systemmentioning
confidence: 99%
“…DLB has previously been mistakenly diagnosed as Alzheimer's disease and sometimes has been confused with schizophrenia. One of the major problems in the performance of clinical trials with DLB is the correct diagnosis of the disorder [23,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation